FecB mutation responsible for fecundity in sheep not detected in Indian goats- a short note - Ahlawat, Sonika; Sharma, Rekha; A Maitra (Journal of Livestock Biodiversity, 2025)
Goats contribute appreciably to the livelihoods of the livestock-keeping households, especially of marginal and low input farmers, many of whom have scanty resources beyond their small holdings and livestock. In addition, goats are important to the subsistence family food requirements as they provide abundant and regular supply of meat, milk, fur and cashmere. Hence a moderate increase in litter size can lead to larger profit to the rural poor. Improvement of reproduction by traditional selective breeding methods has proved to be difficult due to low heritability and long reproductive cycle. Thus the candidate gene approach provides an alternate tool for early breeding that can accelerate the improvement of goat reproduction. Genetic studies on sheep prolificacy across continents have indicated that litter size and ovulation rate are determined by the action of single gene, named fecundity (Fec) genes, with major effects. FecB was the first major gene for prolificacy identified in Australian Merino sheep. Since the tendency of twining and triplets is inherited and possibly common in the two small ruminants (sheep and goat), the objective of this study was to screen Indian goats for FecB mutation so as to validate if the same mutation is responsible for prolificacy of goats also.